Fire spalling of ultra-high performance concrete: From a global analysis to microstructure investigations. (January 2019) - Missemer, L.; Ouedraogo, E.; Malecot, Y.; Clergue, C.; Rogat, D.
Abstract: This article presents the behaviour under fire of a specific ultra-high performance concrete (UHPC) called BCV. Several compositions with synthetic additions such, as polypropylene (PP) fibres and powder or acrylic (PAN) fibres, are mixed to produce these specimens. As a first step, a blowtorch test on prismatic specimens shows that small PP fibres are more efficient in resisting fire. Next, scanning electron microscopic observations after heating reveal significant behavioural differences between PP fibres and PAN fibres during their vaporisation process. Lastly, a mercury intrusion porosimetry investigation following a heating cycle at 350°C indicates that concrete porosity is not a sufficient parameter for determining whether or not a given material composition is resistant to fire spalling. A critical factor dependent on pore size distribution, is proposed herein; its threshold value, i.e. under which the material exhibits a very high probability of being prone to fire spalling, is also estimated.